BUILDING SOFTWARE TEST PROBLEMS IN PUBLIC SECONDARY SCHOOL FOR USING MICROSOFT VISUAL BASIC 6.0 - Yayat Yayat (Jurnal Sistem Informasi, 2005)
In this writing contains about problems that arise in the process of accepting new students at the High School, in the case of entry exams for the selection of prospective students will be accepted,. The author proposes a software / software that can be used in the selection process, namely in the form of applications that computerized exam and connected into computer networks. With this software, processes and manufacturing penilain prospective graduation list of students can be done more quickly and accurately. The final part of the writing of programs is attached as supporting the proposed application.